BAHAN PANGAN LOKAL BERBASIS TUMBUHAN LIAR DI PASAR IBUAH KOTA PAYAKUMBUH - Wahyu Ningsih; Hernawati Hernawati (Ensiklopedia Research and Community Service Review, 2026)
Traditional communities living around Payakumbuh City, Lima Puluh Kota Regency, West Sumatra, possess traditional knowledge in utilizing wild plants as local food ingredients. Local food ingredients in traditional culinary have the potential to be developed into functional foods. The purpose of this study was to identify edible wild plant species sold at Ibuah Market, Payakumbuh. This study used a qualitative descriptive method with an ethnobotanical approach. Data were collected through interviews with informants, observation, and documentation of plant morphological characteristics. Wild plants used as local food ingredients were identified to determine their scientific names. There are 21 species of wild plants used by the community around Payakumbuh City and sold at Ibuah Traditional Market, grouped into 21 families. The most commonly used plant parts are leaves, fruits, flowers, stems, and shoots. Wild plants are sold in raw or processed form. The plant species sold in processed form are Dendrocalamus asper (robuang) and Pangium edule (simauang). The wild plants sold as food ingredients at Ibuah Market come from several areas around Payakumbuh City which are located close to the forest. Keywords:  Wild edible plants, food ingredients, functional food,  traditional market, Pasar Ibuah